Modular ceramic scaffolds for individual implants. (15th October 2018) - Biggemann, Jonas; Pezoldt, Marc; Stumpf, Martin; Greil, Peter; Fey, Tobias
Graphical abstract: Abstract: Ideal artificial bone grafts aim for multiscale porosity, high mechanical strength and ensure rapid vascularization for bone ingrowth. In this work modular ceramic arteriovenous loops (AV-loops) with a hierarchical porosity approach were designed and manufactured to meet these criteria and to exceed the poor mechanical strength of monolithic scaffolds. Bioactive building blocks (β-TCP, HAp, BCP) with dimensions of 1.5–3.0 mm were prepared by injection molding and assembled to complex AV-loop scaffolds using a customized automated assembly technology (pick and place). The building blocks were bonded with a biocompatible adhesive. Single building blocks are characterized by a compressive strength of 112.4–134.5 MPa with a residual sintering porosity of 32.2–41.5%, matching the strength of cortical bone of 100–230 MPa. The compressive strength of the modular assemblies varied between 22.3 and 47.6 MPa primary depending on the building block arrangement. The achieved compressive strengths are superior to current monolithic AV-scaffolds and sufficient for the implantation as non-load-bearing AV-loop scaffolds in isolation chambers. The modular AV-loop scaffolds provide a hierarchical interconnected pore network (P = 58.8%) combining small macropores of 4.1–4.3 µm size for possible enhanced protein absorption and large gradient macropores of 200–1700 µm size for optimum vascularization and complete bone ingrowth. The modular building block approach allows to design patient individualized scaffolds with complex hierarchical pore networks. The pore volume, size and geometry as well as the biological response can effectively be tuned by changing the dimensions, shape and placing gap of the bioactive building blocks. Statement of Significance: Gold standard of bone replacement in case of surgery or cancer is still own bone material usually taken from the hip/arm or leg in second surgery with poor mechanical properties and limited amount. To avoid a second surgery and provide mechanical strong scaffold structures for fast patient regeneration a novel modular building block approach is used. This allows complex scaffold geometry with a hierarchical interconnection porosity for blood vessel ingrowth. The pore volume, size and geometry as well as the biological response can effectively be tuned by changing the dimensions, shape and placing gap of the bioactive building blocks.